FAKTOR YANG MEMPENGARUHI PROFITABILITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Fanny, Sufiyati M. F. Djeni Indrajati W (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is examine the analysis of factors affecting profitability of manufacture companies listed on Indonesia Stock Exchange for the period 2016-2018. Sample was selected using purposive sampling method amounted to 74 companies. Data processing techniques using multiple regression analysis that helped by EViews 10 program and Microsoft Excel 2016. The result of this study shows that partially working capital management and volume of capital have significant effect on profitability, while human capital efficiency, structural capital efficiency, capital employed efficiency and asset tangibility have no significant effect on profitability. However, this study shows that simultaneously working capital management, human capital efficiency, structural capital efficiency, capital employed efficiency, asset tangibility and volume of capital have a significant effect on profitability.